1993
DOI: 10.1093/bja/70.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catecholamines and Neonatal Condition After Induction of Anaesthesia With Propofol or Thiopentone at Caesarean Section

Abstract: Increased maternal sympathetic nervous system activity may decrease placental perfusion and cause adverse neonatal effects. We have studied the catecholamine response and neonatal outcome in Chinese patients with uncomplicated, singleton pregnancies undergoing Caesarean section. Anaesthesia was induced with thiopentone 4 mg kg-1 (n = 32) or propofol 2 mg kg-1 (n = 30) followed by suxamethonium. Laryngoscopy was performed after 1 min and tracheal intubation completed by 2 min. Anaesthesia was continued with atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 0 publications
2
26
0
4
Order By: Relevance
“…There have been several studies comparing propofol to thiopental for induction of anaesthesia for elective Caesarean section [20][21][22][23][24][25][26][27][28][29][30]. These have showed little difference in neonatal Apgar scores or umbilical blood gas analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies comparing propofol to thiopental for induction of anaesthesia for elective Caesarean section [20][21][22][23][24][25][26][27][28][29][30]. These have showed little difference in neonatal Apgar scores or umbilical blood gas analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These have showed little difference in neonatal Apgar scores or umbilical blood gas analysis. Two studies [21,22] observed signs of lighter anaesthesia in the propofol group; however out of 516 women randomly allocated to propofol or thiopental [20][21][22][23][24][25][26][27][28][29][30] there were two episodes of recall, both occurring with thiopental [20,27]. Three studies [24,27,29] suggested an improved maternal recovery with propofol while four [20][21][22]30] found no difference.…”
Section: Resultsmentioning
confidence: 99%
“…For example, remifentanil, a rapid and short-acting opioid, has been successfully used to attenuate the hemodynamic and catecholamine responses following tracheal intubation in severe preeclamptic patients undergoing cesarean delivery. 11 Propofol also attenuates the pressor responses associated with laryngoscopy 12,13 and has no adverse effects on maternal hemodynamics, umbilical cord blood gases, Apgar scores and neurobehavioral scores. 13 In our case, we used only propofol (1.5 mg/kg) during anesthesia induction.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery facilitated the prone position and decreased the risk of epidural bleeding. 12 Also, the fetus was spared exposure to radiation during spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although cardiac inhibition and vasodilation from propofol may produce hypotension and bradycardia, [11][12][13] other commonly used general anesthetics, including thiopental, are similar. 11,14,15 For example, Mouren et al reported that propofol did not inhibit the myocardial performance of a blood-perfused isolated heart, but that thiopental did. 16 Therefore, cardiac inhibition or vasodilation might not be the only factor in the inhibition of hypertension and tachycardia which can be found during tracheal intubation with propofol anesthesia.…”
Section: Response To Intubationmentioning
confidence: 99%